Strategi Komunikasi dalam Mengatasi Perubahan Iklim melalui Pelibatan Masyarakat - Mukhammad Fatkhullah; Iwed Mulyani; Armoni Suci Dewi; Muhammad Alhada Fuadilah Habib; Audina Reihan (Institut Pertanian Bogor, 2023)
Program Kampung Iklim aims to encourage the participation of the community and other stakeholders to take action regarding climate change. This study aims to describe communication strategies implemented to increase participation from local governments, communities, and other stakeholders. This research was conducted by desk research with a qualitative approach, and using Strategic Framework Analysis (SFA) as an analytical tool. Analysis carried out on statutory documents, roadmaps, socialization materials, monitoring, evaluation, as well as annual and long-term reports. The results showed that the communication strategy in ProKlim focused on increasing community participation. Context refers to climate hazards that can threaten the sustainability of humankind. Thus, the community must play an active role in handling climate change by adapting and mitigating. The number refers to the increase in temperature per year where the average temperature in 2016 was 1.2ºC higher than the average temperature in 1981-2000. Through visualization, metaphors, and the use of appropriate tones, ProKlim is presented to the public as a persuasive program. Unfortunately, the dissemination is still delivered in a formal and limited way. Thus, it can be concluded that the low community participation in ProKlim is due to the fact that the information conveyed is still formal and does not take place continuously.